Longitudinal collision risk for ATC track systems: a hazardous event model - Brooker, Peter (Cambridge University Press, 2006)
This paper presents a collision risk model and operational concepts for longitudinal separated aircraft in the North Atlantic Region air traffic control track system, and indicates how it might be used to reduce separation minima safely, and hence deliver cost savings. It is an event-based model: it is easy to see what is being assumed, to understand the role of the main parameters, and to incorporate collision detection and hazard analysis. A potential future operation, with a 7-minute separation and a strategic lateral offset system, is sketched using the model.